The party's over at the digital society: some thoughts towards the search for serious theoretical frameworks. (2016) - Burke, Maria E.
There has been much in the way of excitement and celebration concerning all things 'digital', which has provided the opening 'context' of the 21st century. We now need to stop, take a break and think clearly about our newly emerging areas. This paper's aim is to provide a discussion of the need for a robust theoretical framework for an idea embraced by the digital society - that all things, i.e., artefacts, - are connected by a story or a memory to each other and to people, resulting in an all consuming 'internet of things'. The paper introduces a new project 'The Search for New Frameworks for Digital Research' based at the University of Winchester at Winchester, UK and offers definitions of the area and key terms followed by initial thoughts about how other disciplines choose theoretical frameworks.